« Tuer pour saisir la vie » : neutralisation épistémologique et politique des animaux dans l’Antiquité - Benedetta Piazzesi (Cahiers d’histoire.)
This interview focuses on different aspects of the animal question in ancient Greek thought. Retracing the intellectual background of the interviewee, we show the emergence of a new historiographical and philosophical interest in animals in ancient societies from the 1970s onwards, questioning the theoretical perspectives of Marxism, historical epistemology and structuralism. The authors examine the transformation brought about by Aristotle’s thought in the scientific study of animals and the new techniques associated with it, in particular the anatomical dissection of their bodies. Finally, this relationship is questioned in its epistemological and political stakes in relation to modern breeding technologies.